Avaliação dos serviços prestados pelos consórcios públicos intermunicipais de Minas Gerais na perspectiva de gestores de saúde - Marcus Vinicius da Silva Costa (2023)
Introduction: one of the principles of the Unified Health System (UHS) is the decentralization of health services, with a single direction in each sphere of government and states and municipalities having shared responsibility for the management of public policies. Municipal autonomy became more feasible through cooperation agreements between entities interested in achieving the same objective. This cooperation results in interfederative consortia, which are voluntary associations whether through municipalities, states and/or unions. As in other regions of the country, health consortia in Minas Gerais exist due to a need for municipalities to come together, as alone they would not be able to provide a certain type of service to society. Evaluation needs to be thought of not only as a judgment of the service being provided, but also as an opportunity for change. Objective: to evaluate the services provided by Intermunicipal Health Consortia in Minas Gerais from the perspective of municipal managers. Methodology: from a methodological point of view, this is a research with a qualitative approach, which was carried out with municipal health managers in the state of Minas Gerais in the 14 Health Macroregions. Data were collected through interviews with a semi-structured script, from February to September 2023. The project was submitted to the Research Ethics Committee of the Federal University of Minas Gerais and data collection only began after approval. The interviews took place between March and September 2023, using a semi-structured script. Considering that this is research for a Professional Master's Program and the short time for the research, a pre-defined number of 14 participants was chosen. The interviews were recorded, listened to in full, transcribed and submitted to Content Analysis, following the Thematic Analysis modality. Results and discussion: three categories of analysis were organized: the first addresses the participation of consortia in the Health Care Network, which was related to referral and counter-referral, Elective Health Transport, specialized care and purchase of medicines. In the second category, the scope of the proposed purposes was presented, addressing specialized care and the health consortium as an important tool for small municipalities. In the third and final category, the strengths and weaknesses were presented, with emphasis on the discussion of points such as the distance from the consortium, the value of the procedures, the variety of procedures and the quality of the service. The study revealed that participants recognize the importance of the consortium for the integration of the Health Care Network. However, even knowing the importance of consortia, services are not always provided in the best way for SUS patients. Final considerations: during this study, it became evident the need for managers to understand the Health Care Network and know the importance that consortia have in the network to help municipalities provide services to the population. It is worth noting that the health consortium represents a valuable strategy that can help municipalities strengthen their flow within the Health Care Network.